Recasting Culture to Undo Gender : A Sociological Analysis of Jeevika in Rural Bihar, India - Sanyal, Paromita; Rao, Vijayendra; Majumdar, Shruti (World Bank, Washington, DC, 2015)
This paper brings together sociological theories of culture and gender to answer the question – how do large-scale development interventions induce cultural change? Through three years of ethnographic work in rural Bihar, the authors examine this question in the context of Jeevika, a World Bank-assisted poverty alleviation project targeted at women, and find support for an integrative view of culture. The paper argues that Jeevika created new “cultural configurations” by giving economically and socially disadvantaged women access to a well-defined network of people and new systems of knowledge, which changed women’s habitus and broke down normative restrictions constitutive of the symbolic boundary of gender.